(untitled) (mathematica didactica, 2021)
Using the example of the geometric concept of the cube, we will illustrate how conceptual developmental processes within a mathematical learning environment using 3D printing technology can influence students’ learning and learning processes. As the basis of description, the descriptive concept Subjective Domains of Experiences and the idea of the so-called Basic Mental Models, which is intended as a normative guideline, are mutually related. Paradigmatic examples show that this approach may also be useful for further research of conceptual development.